1995
DOI: 10.1002/j.1460-2075.1995.tb07134.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of chromosomal proteins HMG-14/HMG-17 into nascent nucleosomes induces an extended chromatin conformation and enhances the utilization of active transcription complexes.

Abstract: The role of chromosomal proteins HMG‐14 and HMG‐17 in the generation of transcriptionally active chromatin was studied in a Xenopus laevis egg extract which supports complementary DNA strand synthesis and chromatin assembly. Chromosomal proteins HMG‐14/HMG‐17 enhanced transcription from a chromatin template carrying a 5S rRNA gene, but not from a DNA template. The transcriptional potential of chromatin was enhanced only when these proteins were incorporated into the template during, but not after, chromatin as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
5

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 69 publications
5
98
5
Order By: Relevance
“…[The increase in the repeat length in the presence of HMG17 might be related to the finding that phosphorylated HMG14/17 can, under certain conditions, increase the repeat length of reconstituted chromatin from 145 to---160--165 bp (Drew 1993;Tremethick and Drew 1993}, but it is difficult to compare the data because of the significant differences in the chromatin reconstitution systems used in the other work. Note also that our observation of the increase in the repeat length in the presence of HMG 17 is in contrast to the interpretation of the micrococcal nuclease digestion data of previous studies, wherein it was concluded that incorporation of HMG14/17 into chromatin does not affect the repeat length (Crippa et al 1993;Trieschmann et al 1995). We suggest, however, that the differences may be in the interpretation of the data because in the earlier work, the micrococcal nuclease digestion ladders contained only three or four bands, which led to difficulty in the determination of the nucleosomal repeat lengths.]…”
Section: Hmg17/180 Bpcontrasting
confidence: 99%
See 2 more Smart Citations
“…[The increase in the repeat length in the presence of HMG17 might be related to the finding that phosphorylated HMG14/17 can, under certain conditions, increase the repeat length of reconstituted chromatin from 145 to---160--165 bp (Drew 1993;Tremethick and Drew 1993}, but it is difficult to compare the data because of the significant differences in the chromatin reconstitution systems used in the other work. Note also that our observation of the increase in the repeat length in the presence of HMG 17 is in contrast to the interpretation of the micrococcal nuclease digestion data of previous studies, wherein it was concluded that incorporation of HMG14/17 into chromatin does not affect the repeat length (Crippa et al 1993;Trieschmann et al 1995). We suggest, however, that the differences may be in the interpretation of the data because in the earlier work, the micrococcal nuclease digestion ladders contained only three or four bands, which led to difficulty in the determination of the nucleosomal repeat lengths.]…”
Section: Hmg17/180 Bpcontrasting
confidence: 99%
“…Hence, the structural analysis revealed that HMG 17 was efficiently and properly incorporated into chromatin that was assembled with double-stranded, circular plasmid DNA, and these data thus indicate that the HMG17-mediated transcriptional activation was not attributable to a general inhibition of chromatin assembly. In other work, a Xenopus egg extract was used to prepare HMG17-containing chromatin for the analysis of the effect of HMG 17 on transcription by RNA polymerase III (Crippa et al 1993;Trieschmann et al 1995). In those experiments, chromatin was generated from a single-stranded-circular DNA template by a coupled DNA replication (complementary strand synthesis)-chromatin assembly process that was carried out in the absence of Mg(II)-ATP.…”
Section: Hmg17/180 Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin condensation is controlled by several factors, including reversible acetylation of histone H3 and H4 (Allfrey et al 1964;Turner 1991;Lee et al 1993;Loidl 1994;Braunstein 1996;Roth and Allis 1996;Grunstein 1997;Wade et al 1996;Mizzen and Allis 1996), methylation of DNA cytosine in position 5 (Cacciamani et al 2002), interactions with HMG (Crippa et al 1993;Paranjape et al 1995;Trischmann et al 1995;Ding et al 1997;Klosterman and Hadwiger 2002) or polycomb proteins (Preuss 1999) and with histone H1 (Wolffe 1997;Dou and Gorovsky 2000) The last one is involved in the first level of chromatin condensation, therefore its role seems especially relevant.…”
Section: Introductionmentioning
confidence: 99%
“…It was known that HMG 14/17 proteins could enhance the replication and transcription when the chromatin was used as template [20].…”
mentioning
confidence: 99%